Bendamustine‐based conditioning prior to autologous stem cell transplantation (ASCT): Results of a French multicenter study of 474 patients from LYmphoma Study Association (LYSA) centers. Issue 6 (14th March 2018) - Chantepie, Sylvain P.; Garciaz, Sylvain; Tchernonog, Emmanuelle; Peyrade, Frederic; Larcher, Marie‐Virginie; Diouf, Momar; Fornecker, Luc‐Mathieu; Houot, Roch; Gastinne, Thomas; Soussain, Carole; Malak, Sandra; Lemal, Richard; et al.
Abstract: Carmustine shortage has led to an increase use of alternative conditioning regimens prior to autologous stem cell transplantation for the treatment of lymphoma, including Bendamustine‐based (BeEAM). The aim of this study was to evaluate the safety of the BeEAM regimen in a large cohort of patients. A total of 474 patients with a median age of 56 years were analyzed. The majority of patients had diffuse large B‐cell lymphoma (43.5%). Bendamustine was administered at a median dose of 197 mg/m 2 /day (50‐250) on days‐7 and −6. The observed grade 1‐4 toxicities included mucositis (83.5%), gastroenteritis (53%), skin toxicity (34%), colitis (29%), liver toxicity (19%), pneumonitis (5%), and cardiac rhythm disorders (4%). Nonrelapse mortality (NRM) was reported in 3.3% of patients. Acute renal failure (ARF) was reported in 132 cases (27.9%) (G ≥2; 12.3%). Organ toxicities and death were more frequent in patients with post conditioning renal failure. In a multivariate analysis, pretransplant chronic renal failure, bendamustine dose >160 mg/m 2 and age were independent prognostic factors for ARF. Pretransplant chronic renal failure, hyperhydration volume, duration of hyperhydration, and etoposide dose were predictive factors of NRM. A simple, four‐point scoring system can stratify patients by levels of risk for ARF and may allow for a reduction in the bendamustine dose to avoid toxicity. Drugs shortage may have dangerous consequences. Prospective, comparative studies are needed to confirm the toxicity/efficacy extents from this conditioning regimen compared to other types of high dose therapy.